Perancangann Alat Pembuat Pellet Karbon Aktif dengan Kapasitas Gaya 2 Ton - G.R.A.L.,, Paul H.; Widiyarta, I M.; Putra Negara, D.N.K. (Teknik Desain Mekanika, 2021)
Abstract Activatedicarboniis knownias a universal adsorbent while activated carbon pellets are made by extruding activated carbon powder into a cylindrical tube. In the use of activated carbon pellets, its content makes it ideal for applications in the industrial sector that has air/gas waste. Activated carbon pellets which are currently widely used in the community are considered capable and can be a solution to overcome air pollution caused by CO2. Hydraulics is the study of the flow of liquids through closed pipes and vessels, as well as in open canals and rivers. In the industrial world the use of hydraulic systems is very widely used because it is very helpful in that sector. In this design process, the aim is to create a carbon pellet maker made of activated carbon. In the end, this tool uses hydraulic power in the pressing process to make active carbon pellets. Gayaoyango produced by canopads and piston cylinder N has a maximum thrust capacity of 2 tons. The result of this design process is a press tool with dimensions that are 16.4 cm x 11.4 cm x 46.3 cm. The test is carried out with variations in pressure, the pressures given are 14 Psi, 15 Psi, 16 Psi, 18 Psi, 20 Psi, 23 Psi, 25 Psi, and 27.2 Psi. The minimum pressure given so that the pellet does not break is 20 Psi, at a pressure of 14 Psi to 18 Psi the pellet does not form properly and breaks. The forces received by each pellet are 3.48 N, 7.37 N, 10.83 N, and 11.68 N. Keywords: activated carbon, pellets, hydraulics, design, efficiency